Now look what you've done - Pastis, Stephan (Pastis, Stephan. Timmy Failure, 2016)
After being born and founding an empire, Timmy Failure is back to solve the biggest mystery of his generation--only he has competition in this endeavor, and their humorous shenanigans might be the only thing that can stop him.